The Influence of Character Education on Students' Learning Achievement at SMP Negeri 1 Seyegan - Setya, Raudya; Handoyo, Eko; Suyahmo, Suyahmo; Purnomo, Arif (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Y, 2024)
This research aims to examine the influence of character education on student learning achievement at SMP Negeri 1 Seyegan. Character education is an important aspect in the educational process which not only focuses on intellectual development, but also on forming students' morals and ethics. In this research, a character education program was implemented that integrated values such as discipline, responsibility, hard work and honesty into the curriculum and daily activities at school. The research method used is a qualitative method with a case study approach. Data was collected through observation, interviews and documentation. Participants in this research were students, teachers and administrative staff at SMP Negeri 1 Seyegan. Data analysis was carried out descriptively to evaluate the impact of character education on student academic achievement. The results of the research show that the implementation of character education at SMP Negeri 1 Seyegan contributes significantly to increasing student learning achievement. Students involved in character education programs show higher learning motivation, better discipline, and more developed critical thinking skills. Apart from that, the positive and supportive learning environment created through character education also plays a role in increasing student involvement and participation in the learning process.